2018
DOI: 10.1590/2317-1545v40n2188120
|View full text |Cite
|
Sign up to set email alerts
|

Association between the artificial aging test and the natural storage of coffee seeds

Abstract: -The accelerated aging test is recognized as an efficient method for evaluating the vigor of seed lots and for estimating their storage potential. Thus, this work aimed to evaluate the association between artificial aging and natural storage of coffee seeds, through the correlation factor analysis. Seeds of four cultivars of Coffea arabica L. (Catuaí Amarelo, Arara, Catiguá, and Mundo Novo) and one of Coffea canephora Pierre (Apoatã) were used. Part of the newly-harvested seeds were aged in a growth chamber un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 19 publications
2
9
0
Order By: Relevance
“…Drying is a critical step in the postharvest process (Fantazzini et al, 2018;Freitas et al, 2018;Osorio et al, 2016). In this context, the main risks that may arise are biological and chemical, and these may result in a product that is unfit for human consumption (Osorio et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Drying is a critical step in the postharvest process (Fantazzini et al, 2018;Freitas et al, 2018;Osorio et al, 2016). In this context, the main risks that may arise are biological and chemical, and these may result in a product that is unfit for human consumption (Osorio et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…However, almost all above studies only focused on artificial seed aging. Moreover, previous published research has proved that artificially aged seeds display amplified deterioration in comparison with naturally aged seeds (Petruzzelli and Carella, 1983;Giurizatto et al, 2012;Fantazzini et al, 2018) and are associated with a higher prediction accuracy. In addition, all these researches are destructive, and limited research has been conducted for naturally aged seed deterioration.…”
Section: Introductionmentioning
confidence: 98%
“…Few references appear in the scientific literature on using the accelerated aging test to evaluate the physiological conditions of Coffea arabica L. seed lots. Pertel et al (2003) and Fantazzini et al (2018) worked with the accelerated aging test at the temperature of 42°C and different exposure times for coffee seeds. They observed that seed deterioration occurred over long periods of exposure, indicating that other ambient conditions within the aging chamber should be investigated.…”
Section: Introductionmentioning
confidence: 99%